Estimation in single-index varying-coefficient panel data model. Issue 12 (20th May 2022) - Wang, Tonghui; Wang, Liming; Zhou, Xian
Abstract: In this paper, we study the single-index varying-coefficient panel data model. Combining the refined minimum average variance estimation (RMAVE) method with the local linear regression, we estimate the parameters in single index and link function, and explain the steps of the iterative algorithm. Under certain regularity conditions, the asymptotic properties of the estimators of the parameters and link functions are derived. Finally, numerical simulations are presented and our model is shown to perform better than the single-index panel data model in a real-data example.